Teoria i praktyka socjalizacji politycznej w edukacji wczesnoszkolnej – demokracja kontra neoliberalizm - Hildebrandt-Wypych, Dobrochna (Studia Edukacyjne, 2017)
The text focuses on the efficiencyof school as one of the key agents of political socialization of early childhood students. Using the conceptual framework of J. Astuto and M.D. Ruck, a question is posed of how to effectively develop prosocial skills of children and therefore how to shape their later willingness to engage in civic actions in youth. According to various scholars, prosocial skills, such as respect for others’ feelings, helping, sharing and cooperating with others, have to be nurtured through classroom-based play. Unfortunately, in the age of neoliberal dominance of standardized tests, civic education is deemed less important, with an excessive focus on civic knowledge and the insufficien (not testable) focus on civic skills. In reference to research results (e.g. C. Flanagan and L.S. Gallay), the author of the article points out that democratic competence does not simply emerge as a result of top-down transmission of knowledge. The process of normative (moral) development in childhood knowledge of political facts is significantlyless important than the child’s social experience of civic participation and cooperation. Contrary to the neoliberal tendencies in educational reforms, democracy-learning – as pointed out by numerous studies – should be based on the development of a ‘democratic self’ (values, patterns of behavior, habits), prior to the development of political knowledge. Knowledge should be treated as a second important element of school political socialization of children. The primary focus should be the school’s commitment to the development of children’s democratic attitudes.